Development of Nahwu Learning Media Based on Genially and Handout - Rahmawaty, Nurul; Hulwani, Yusuf; Aisyahrani, Diva Prima; Mustofa, Ady Muh. Zainul; Sanusi, Anwar (Al-Lahjah : Jurnal Pendidikan, Bahasa Arab, dan Kajian Linguistik Arab, 2025)
This research aims to develop learning media that can be used as an alternative to help students learn independently outside of class hours, so that it is expected to improve their learning outcomes. The type of research used is development research (Research and Development) by applying the ADDIE development model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. This research was conducted at MTs Pondok Pesantren Al-Hidayah Jambi, with the research subjects being students at the institution. Data collection techniques were carried out through learning outcomes tests, interviews, and observations of the process of using the media. The data obtained were analyzed using quantitative and qualitative approaches to determine the effectiveness of the media and students' responses. The results showed that 57% of students were able to answer the questions correctly, indicating that the learning media developed was in the good category. Based on interviews, learners stated that this media is feasible and helps in the process of independent learning outside the classroom. This finding shows that the developed learning media has the potential to support the improvement of learning outcomes and strengthen students' learning independence.